Sustained Adrenergic Signaling Promotes Intratumoral Innervation through BDNF Induction - Allen, Julie K; Armaiz-Pena, Guillermo N; Nagaraja, Archana S; Sadaoui, Nouara C; Ortiz, Tatiana; Dood, Robert; Ozcan, Merve; Herder, Danielle M; Haemmerle, Monika; Gharpure, Kshipra M; Rupaimoole, Rajesha; Previs, Rebecca A; et al. (Cancer research (Chicago, Ill.), 2018)
Mounting clinical and preclinical evidence supports a key role for sustained adrenergic signaling in the tumor microenvironment as a driver of tumor growth and progression. However, the mechanisms by which adrenergic neurotransmitters are delivered to the tumor microenvironment are not well understood. Here we present evidence for a feed-forward loop whereby adrenergic signaling leads to increased tumoral innervation. In response to catecholamines, tumor cells produced brain-derived neurotrophic factor (BDNF) in an ADRB3/cAMP/Epac/JNK-dependent manner. Elevated BDNF levels in the tumor microenvironment increased innervation by signaling through host neurotrophic receptor tyrosine kinase 2 receptors. In patients with cancer, high tumor nerve counts were significantly associated with increased BDNF and norepinephrine levels and decreased overall survival. Collectively, these data describe a novel pathway for tumor innervation, with resultant biological and clinical implications. Sustained adrenergic signaling promotes tumor growth and metastasis through BDNF-mediated tumoral innervation. .